HANDLING OF ILLEGAL LEVIES BY THE TASK FORCE TO CLEAN UP ILLEGAL LEVIES IN INDONESIA (REVIEWED FROM THE ASPECTS OF PLANNED BEHAVIOUR AND TECHNOLOGY) - Putro, Gamal Haryo; Widodo, Pujo; Zauhar, Soesilo; Wijaya, Andy Fefta; Hermawan, Romy; Wasitova, Lilly (The journal of contemporary issues in business and government, 2022)
Illegal levies such as ingrained in people's daily activities, and not infrequently, illegal levies are considered something that is commonly done in Indonesia. This study discusses the handling of unlawful levies carried out by the Illegal Levy Clean Up Task Force, including effectiveness and obstacles, as well as handling solutions with a planned behavior and technology approach. This research uses a qualitativeresearch approach, where the data collection used is an interview, observation,and documentation methods which are then analyzed with interactive model data analysis techniques. The results of this study show that illegal levies continue to occur in the community due to the non-optimal enforcement caused by several obstacles such as the condition of the Illegal Levy Clean Up Task Force, which is not law enforcement, the lack of derivative rules, the establishment of an ineffective illegal levy eradication unit, the occurrence of multiple positions, and low community participation. The handling of illegal levies in terms of planned behavior aspects is carried out through socialization, rules, and an ecosystem of control functions that close space for illegal levy activities. Other things that need to be done to deal with illegal levies are establishing a whistleblowing system, strengthening witness protection, the obligation to form derivative rules, and handling illegal levies in a multilevel manner. In addition, technological aspects can also support the implementation of effective handling of illegal levies. The Illegal Levy Clean Up Task Force can establish a prevention system to accelerate coordination, mapping, and evaluation in eradicating illegal levies.